(untitled) (Revista de Medicina Clinica, 2023)
Introduction: Potts disease is an extrapulmonary activation of a latent infection by Mycobacterium tuberculosis, mainly affecting vertebral bodies and adjacent tissues. Generally, the activation occurs years after the primoinfection. The clinical presentation groups a vast variety of symptoms, making it a difficult task to reach the proper diagnosis, and to resolve the chronic complications of locoregional inflammation that lead to spinal destruction. Case Report: A previously healthy 65-year-old Mexican woman with controlled hypertension and osteoporosis, with no prior BCG vaccine, presented to the hospital with complaints of progressive chronic lumbar pain, with mild control upon NSAID administration. On a CT scan, a right paravertebral cold abscess was identified at the T9-T10 level with bony destruction that eventually progressed to lower extremity paraplegia, regardless of antibiotic therapy. Invasive procedures (abscess drainage and spinal decompression) helped with the identification of tuberculous infection, starting anti-TB combination therapy that lead to clinical recovery. Conclusion: Even though it is a rare disease, among highly endemic countries, clinicians will eventually face this pathology. The description of this case report adds more information to the clinical archives of Potss Disease, as well as a brief literature revision on the topic.